Sistema inteligente para la gestión del ahorro energético, confort y seguridad de la microempresa “Amalac” de la parroquia Guaytacama, cantón Latacunga provincia de Cotopaxi - Tipán Tasinchana, Carlos Santiago (2017)
The concept of home automation has evolved along with technological advancement of electronics focused on the areas of control and communications, in the quest to meet the needs and well-being of people in interaction with the home. The present project focuses on the creation of a domotic system, of remote type and of easy manipulation for the users of the microcompany AMALAC Food Processor. The proposal to create a home automation system with monitoring and control capability in the areas of lighting, comfort and security, through the use of various types of wireless communication such as: Bluetooth, Wi-Fi and GSM is evaluated. The system developed in this project is characterized by a communication architecture in the form of a star, with a tablet as a central node that is responsible for the control and monitoring of the entire system, through the application developed for the Android operating system In charge of managing devices locally, and at the same time the creation of a web system that is in charge of monitoring remotely....